2017
DOI: 10.1155/2017/7496934
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, SAR, and Docking Studies Disclose 2-Arylfuran-1,4-naphthoquinones as In Vitro Antiplasmodial Hits

Abstract: A total of 28 lapachol-related naphthoquinones with four different scaffolds were synthesized and spectroscopically characterized. In vitro antiplasmodial activity was assayed against the chloroquine-resistant Plasmodium falciparum W2 strain by the parasite lactate dehydrogenase (pLDH) method. Cytotoxicity against Hep G2A16 cell was determined by the MTT assay. All compounds disclosed higher in vitro antiplasmodial activity than lapachol. Ortho- and para-naphthoquinones with a furan ring fused to the quinonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Finally, concerning these series of naphthofuroquinones, it is worth pointing out that many of our compounds are 2-to 5-fold more active against P. falciparum than derivative 6 reported by Borgati et al 12 Among the other evaluated compounds, while lawsone and iodolawsone are weak to very weak inhibitors of P. falciparum in vitro, compounds 28 and 29 seem more interesting. For both couples of compounds bearing either a N-tert-butyl or N-butyl group, the IC 50 values are 1.4 and 1.9 μM, respectively, associated with a weak cytotoxicity (CC 50 > 50 μM) resulting in promising SIs (>36 and >26, respectively).…”
Section: T H I S C O N T E N T Imentioning
confidence: 53%
See 3 more Smart Citations
“…Finally, concerning these series of naphthofuroquinones, it is worth pointing out that many of our compounds are 2-to 5-fold more active against P. falciparum than derivative 6 reported by Borgati et al 12 Among the other evaluated compounds, while lawsone and iodolawsone are weak to very weak inhibitors of P. falciparum in vitro, compounds 28 and 29 seem more interesting. For both couples of compounds bearing either a N-tert-butyl or N-butyl group, the IC 50 values are 1.4 and 1.9 μM, respectively, associated with a weak cytotoxicity (CC 50 > 50 μM) resulting in promising SIs (>36 and >26, respectively).…”
Section: T H I S C O N T E N T Imentioning
confidence: 53%
“…1 H NMR (400 MHz, CDCl 3 ): δ 8.15 (dd, J = 7.6, 1.0 Hz, 1H), 8.02 (dd, J = 7.6, 1.0 Hz, 1H), 7.67 (td, J = 7.5, 1.3 Hz, 1H), 7.59 (td, J = 7.5, 1.3 Hz, 1H), 6.72 (s, 2H), 4.98 (s, 1H), 3.90 (s, 3H), 3.89 (s, 6H), 1.50 (s, 9H). 13 (12). The compound was synthesized by following the above-mentioned general procedure (0.…”
Section: -(Tert-butylamino)-3-(345-trimethoxyphenyl)naphtho-[23-b]fur...mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, Borgati et al [ 83 ] reported a series of four families of compounds issued from structural modifications of the lawsone compound and their in vitro antiplasmodial activities against the chloroquine-resistant P. falciparum W2 strain. The general retrosynthetic scheme of their work is presented below ( Scheme 8 ).…”
Section: Malaria Focused Mitochondrial Targetsmentioning
confidence: 99%